Irregular heat source impact on carreau nanofluid flowing via exponential expanding cylinder: A thermal case study. (August 2022) - Akram, Mohammad; Jamshed, Wasim; Goud, B. Shankar; Pasha, Amjad Ali; Sajid, Tanveer; Rahman, M.M.; Arshad, Misbah; Weera, Wajaree
Abstract: In the Carreau nanofluid (CNF) flow, the transmission of heat through the stretching cylinder is observed in two terms, one is non-linear stretching and other is irregular heat sink/source. In this study we observed thermal radiation and thermal conductivity which depends on temperature. We use similar variables to translate the complex partial differential equations into the ordinary differential equations. By using shooting method (SM), we can find the series solution of the highly order nonlinear ODEs. For some particular results we can compare the series solution with some published results. Two different classes of nanofluids, Aluminum Alloys- Engine Oil (AA7075-EO) and Graphene Oxide -Engine oil (GO-EO) are considered for our analysis. We used some graphs and tables to determine the influence of irregular heat sink/source on heat transformation and movement of fluid for the linear and non-linear stretching rate. From this research we find that non-linear stretching rate and source of heat are causing a disruption of temperature distribution in fluid region. We can improve the velocity and heat profile in the nonlinear situations in all conditions, but not in an internal heat sink. Also, in comparison to the GO-EO, AA7075-EO is the ideal source of heat transfer.